Broadband water-based metamaterial absorber with wide angle and thermal stability - Xiaoqi Zhang; Fengping Yan; Xuemei Du; Wei Wang; Min Zhang (AIP Advances, 2020)
In order to widen the absorption band of the metamaterial absorber to expand its application field, using the electromagnetic characteristics of water in the microwave band, a water-based metamaterial absorber with a structure different from the traditional “metal layer–dielectric layer–metal layer” one is proposed. The numerical simulation results show that its absorptivity of incident electromagnetic waves exceeds 90% in the ultra-wide operating band of 7.84–74.16 GHz and the absorption bandwidth can cover five bands including the X-band, Ku-band, K-band, Ka-band, and U-band. Based on the theories of equivalent medium and impedance matching, the mechanism of broadband absorption was explored by analyzing the electromagnetic field distribution and power loss density of the absorber. The designed absorber has the absorption performance of polarization independence, and it can work under a wide incident angle. In addition, the absorber has excellent thermal stability which can still maintain stable operation when the temperature changes from 0 °C to 100 °C. This water-based metamaterial absorber is of low cost, and its manufacturing process is relatively convenient, so it has broad application prospects in the fields of radar stealth, microwave darkroom, and prevention of electromagnetic radiation.